Inhibition of Potato Polyphenol Oxidase by Halides - B. Patil, Dilip; Kshirsagar, A. (Asian Journal of Chemistry, 2010)
The inhibition of potato polyphenol oxidase catalyzed oxidation of catechol by potassium halides has been carried out on the basis of kinetic measurement. The concentration of catechol was varied in the range of 1.71-8.60 x 10-3 M and that of inhibitor was maintained 4.38 x 10-4 M. The apperent Michaelis constant, Kmapp and dissociation constant of enzymeinhibitor complex, ki were determined at pH 6.80 and temperature 27.0ºC. The potassium halides show competitive type of inhibition. Further, the effect of pH on inhibition was also investigated.